Small is beautiful: diversity of freshwater ostracods (Crustacea, Ostracoda) in marginal habitats of the province of Parma (Northern Italy) - Stefano TAVERNELLI; Valentina PIERI; Claude MEISCH; Koen MARTENS; Giampaolo ROSSETTI (Journal of Limnology, 2006)
A study on the distribution of ostracods in small freshwater habitats of the province of Parma was conducted from May 2004 to December 2005. Vernal pools, ponds, shallow lakes, fountains, springs, ditches, canals, and streams were among the most common types of aquatic systems included in this survey. Altogether, 90 sites located between 24 and 1557 m a.s.l. were visited, and 125 samples were collected. 41 samples did not contain ostracods, and 7 samples were not considered because only immature specimens or empty valves were found. Consequently, 77 samples from 58 sites were analysed. Whenever possible, ostracod identification was done at the species level based on the morphology of both valves and limbs. Thirty-eight taxa from 20 genera belonging to the families Candonidae, Ilyocyprididae, Cyprididae, and Notodromadidae were recorded. This roughly accounts for one-third of the estimated number of non-marine ostracod species in Italy. Scanning electron microscopy images of valves are provided. The maximum number of species per site was six. The most frequent species were Heterocypris incongruens, Eucypris virens, Pseudocandona pratensis, Cypria ophthalmica, and Tonnacypris lutaria. Of particular relevance is the occurrence of species with a limited known distribution in Italy, viz. Ilyocypris monstrifica, Potamocypris villosa, Candona cf. lindneri, Fabaeformiscandona breuili and Physocypria kraepelini. A putative new species of the genus Candona, here left in open nomenclature, is also reported. Our results highlight the importance of so-called "marginal" aquatic habitats as potential biodiversity hotspots, in spite of the general lack of interest shown by freshwater ecologists and taxonomists in undertaking scientific investigations in these environments.